Komunikasi Vertikal dan Horizontal dalam Membentuk Gaya Kepemimpinan Berbasis Kearifan Lokal: Studi pada Binus University - Lidia Wati Evelina; Mia Angeline (Bina Nusantara University, 2014)
Productivity of the company depends on a leader's attempt to control staff via two-way communication. Binus University as a university that relies on IT-based communication has several advantages: cost, distance, and time reduced. However there are also a few problems, such as unreadable nonverbal communication and lack of formality and respect between subordinates and superiors. This study aims to determine vertical and horizontal communication in Binus University which form leadership style based on company local wisdom so that the company may become an institution of higher education that counts. In addition, study aims to determine how corporate culture may establish the company local wisdom in Binus University. Study used descriptive-qualitative method by doing interview and observation to some key informants. Results show that Binus University implements vertical and horizontal flow of information for communication openly and equally within the university. Leadership in Binus always embeds culture that becomes values of Binusian which are composed of 5 points: trust in God, sense of belonging, sense of closing, benchmarking, and continuous improvement in every meeting between leaders and employees. Binus University has also implemented three components forming company local wisdom, namely transformational leadership, culture and corporate structure, and effective knowledge transfer method.